Ecological and Socio-Economic Effects of Highly Protected Marine Areas (HPMAs) in Temperate Waters - Schratzberger, Michaela; Neville, Suzanna; Painting, Suzanne; Weston, Keith; Paltriguera, Lucille (Frontiers in Marine Science, 2019)
This study provides a synthesis of current scientific evidence on the ecological and socio-economic effects of highly protected marine areas (HPMAs), primarily in temperate waters. The aim was to establish if HPMAs can provide benefits beyond those afforded by other types of marine protected area (MPA). We identify critical interactions within and between ecological and socio-economic effects to help marine planners and managers make informed decisions about the trade-offs of alternate management actions or measures for MPAs. Well-designed and enforced MPAs with high levels of protection (HPMAs) often provide conservation benefits within their boundaries beyond those afforded by other types of MPA. Much remains to be learned about the socio-economic effects of HPMAs. Empirical evidence to date suggests that potential benefits cannot all be maximised simultaneously because potentially conflicting trade-offs exist not only between but also within ecological and socio-economic effects. Marine planners and managers must be able to evaluate the impact and distribution of trade-offs for differing management regimes; to make informed decisions about levels of protection required in MPAs to ensure sustainable use of marine resources and meet conservation objectives. One of the main challenges remains providing evidence of the societal benefits from restricting use in these areas.